Multi-criteria analysis in assessment of the degree of degradation pavement elements functional airports made of cement concrete - Wesołowski, Mariusz; Blacha, Krzysztof; Barszcz, Piotr (International Conference “Environmental Engineering”, 2017)
An important factor that affects the safety of flight operations is the proper management of airports, which should be based on the obtained in systematic way information about the state of the surface of the functional elements. One of the characteristic quantities of the technical condition of airport indicator is the assessment of the degree of degradation. It should be noted that the degradation is a slow process extended in time and is the lowering of the properties of the structure by external influences, which in turn generates the changes in their structure. Rating degrade surface should be conducted periodically, which period shall be estimated on the basis of information obtained from the process of the operation of aircraft. Demotions surface is determined on the basis of the type and quantity survey found damage and made repairs. The basis for evaluating the degree of surface degradation is to obtain data from surveys conducted using the method of visual and inventory of them. Research by visual method, despite its apparent simplicity, it is difficult to implement. Qualification of damage or repairs to the appropriate group is often not clear, and therefore the inventory process is described in the documentation of quality management system. The multi-criteria analysis is a method of evaluating the weighted supporting estimating the degree of degradation airfield pavements based on data obtained through inspections performed. Its base is included in the determination of a number of criteria for the selection variant, taking into account different weights to each criterion. The value of the indicator characterizing the degree of surface degradation in relation to estimated criteria allows you to schedule the necessary resources needed to carry out repairs and rational planning of repairs.
Keywords: multi-criteria analysis; airfield pavements; safety of flight operations; degree of degradation